Arm Length and Hand–Eye Coordination Correlates of Underhand Passing at SMA Negeri 1 Sanggau - Wibowo, Agus Tri (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objective:To examine the relationship between arm length and hand–eye coordination with volleyball underhand passing ability among male extracurricular students at SMA Negeri 1 Sanggau. Materials and Methods:A quantitative correlational study was conducted with total sampling of 30 male volleyball extracurricular students. Arm length, hand–eye coordination, and underhand passing performance were assessed using test and measurement instruments. Data were analyzed using Pearson correlation and multiple correlation at α = 0.05. Results:Arm length showed a strong significant correlation with underhand passing (r = 0.826 > r-table = 0.631), while hand–eye coordination was not significant (r = 0.053 < r-table = 0.631). Combined analysis indicated a significant relationship (p = 0.000 < 0.05) with R² = 0.683. Conclusion:Arm length is a key factor associated with underhand passing ability. Although hand–eye coordination alone was not significant, both variables together significantly contributed to underhand passing performance, explaining 68.3% of the variance.